Synthesis characterization and effect of silver nanoparticles on Citrobacter sp. A1 and Enterococcus sp. C1 in simulated environment - Lau, Chew Ping (2017)
Silver nanoparticles (AgNPs) are one of the most widely used commercial nanomaterials due to their antimicrobial properties which could pose as environmental hazard. However, lack of study on the fate and effect of AgNPs released into the environment has prompted this research. Thus, the purpose of this study was to investigate the fate of AgNPs in the environment and also to assess the possible adverse effect of AgNPs on model environmental isolates; Citrobacter sp. A1 (designated A1) and Enterococcus sp. C1 (designated C1). AgNPs capped with polyvinylpyrrolidone (PVP) were synthesized using ultrasound-assisted chemical reduction. It shows that low pH value, high ionic strength and the content of the media influenced the stability of PVP-capped AgNPs. A1 and C1 were contacted with varying concentrations of PVP-capped AgNPs (10, 100, 1000 mg L-1) in nutrient-rich media or 0.1 M phosphate buffer (PB). No significant effect of PVP-capped AgNPs on both A1 and C1 in nutrient-rich media was observed. However, at 1000 mg L-1 PVP-capped AgNPs in 0.1 M PB, A1 retained viability for 6 h while C1 only 3 h. A1 appeared to be more resistant to AgNPs than C1. It is possible that silver ions (Ag+) were released from PVP-capped AgNPs and contributes to the antibacterial effect. The antibacterial mechanism of PVP-capped AgNPs was evaluated. Ag+ or Ag+-adsorbed AgNPs may attack the cell membrane and internalized, leading to bacterial cell death. The effect of the final rinse from a Sharp washer with Ag+ ions releasing function was determined. Although only Ag+ ions were released by the washer, the presence of a mix of AgNPs, Ag ions and other forms of Ag may suggest Ag+ ion transformation. The final rinse water was found to be toxic towards A1 and C1. Additionally, the distribution, transformation and effect of AgNPs under simulated environment containing stream water and sediment was studied. Bacterial consortium of A1 and C1 was introduced into the simulated environment with AgNPs spiked over a period of 50 days. The results revealed that most of the Ag, either PVP-capped AgNPs or Ag+ spiked into the simulated environment migrated from the aqueous phase into the sediment possibly due to aggregation and formation of Ag complexes. The viability of A1 and C1 from the water and sediment in the simulated environment remained unchanged, even at high concentration of AgNPs, at 6500 mg L-1 introduced due to the formation of Ag-organic matter complexes. However, A1 and C1 lost viability when spiked with Ag+ ions exceeding 0.35 mg L-1 which indicates that Ag+ ions were more toxic than AgNPs. It can be speculated that the fate of Ag (either AgNPs or Ag+) is closely tied to the chemistry of the environment into which they are released while the toxic effect of Ag (either AgNPs or Ag+) depends on their fate and the types of bacterial strains present.